Asuhan Keperawatan pada An. E dengan Gangguan Sistem Muskuloskeletal :Post Operasi Open Reduction Internal Fixation Fraktur Klavikula Dextra di Ruang Mawar 2 RSUD Dr. Soeselo Kabupaten Tegal - Rahma Amelia; Ahmad Zakiudin; Tati Karyawati (Jurnal Mahasiswa Ilmu Kesehatan, 2024)
A fracture or what is called a broken bone is an event that often occurs due to trauma or physical exertion which can cause disability and even complications (Appley & Solomon, 2021). The signs and symptoms in fracture patients include pain. The purpose of this writing is to find out and provide nursing care to An. E with musculoskeletal system disorders: post-operative open reduction internal fixation right clavicle fracture in the rose room 2 RSUD dr. Soeselo Tegal Regency in accordance with nursing standards. The methods used are descriptive methods and data collection methods. From the case review, it was found that An's main complaint was. E complains of pain. There were two diagnoses found, namely acute pain, impaired skin and tissue integrity. Interventions are prepared based on the theory of SDKI, SLKI and SIKI as well as on the client's condition and can be implemented.